The Mediating Role of Social Skills in the Relationship between Motor Ability and Internalizing Symptoms in Pre‐primary Children. Issue 2 (4th September 2012) - Wilson, Alicia; Piek, Jan P.; Kane, Robert
<x xml:space="preserve">Abstract</x> Impaired motor development can deprive a child of constructive engagement in early motor activities and thus diminish opportunities for the acquisition of key cognitive, social and emotional abilities. The aim of the current study was to test a model where social skills mediate the relationship between motor ability and internalizing symptoms in pre‐primary children. A cross‐sectional research design was employed to assess the mediation model using data from 234 boys and 241 girls aged 4 to 6 years. Structural equation modelling provided support for the mediating role of social skills as assessed by the child's teacher. Replication of these findings in longitudinal studies, elucidating how social skills relate to motor impairment, could have implications for the prevention of psychopathology in young children with motor impairment. Copyright © 2012 John Wiley & Sons, Ltd.